Establishing three warm‐season turfgrasses with tailored water: II. Root development, nitrate accumulation in plant tissue and soil, and relationship with leaching. Issue 2 (3rd February 2022) - Leinauer, Bernd; Sevostianova, Elena; Velasco‐Cruz, Ciro; Sallenave, Rossana; Serena, Matteo; Horvath, Isabelle; Skerker, Jenny
Abstract: Greenhouse experiments were conducted in 2015 and 2017 to assess the feasibility of establishing three warm‐season grasses—buffalograss [ Buchloe dactyloides (Natt.) Eng.] 'SWI 2000', inland saltgrass ( Distichlis spicata L.), and bermudagrass ( Cynodon dactylon L.) 'Princess77'—with tailored water (tertiary treated effluent with 15 mg L –1 of NO3 –N) and to examine the impact on nitrate accumulation in soils and plant tissue and on root development. Grasses were established from seed in a loamy sand and irrigated with either tailored or potable water plus granular Ca(NO3 )2 fertilizer. Leachate collected at 10‐ and 30‐cm depths was analyzed for NO3 –N and electrical conductivity. Root samples were collected to measure root length density (RLD) and root surface area (RSA). Weekly clippings were collected to determine total clipping yield and measure N content. Generally, there was no difference in establishment, RLD, or RSA between the two irrigation treatments. Highest RLD values were reported for bermudagrass, followed by buffalograss and inland saltgrass. Correlation analyses suggest that nitrate levels in leachate were lower in faster‐growing grasses and in grasses with more extensive root systems, compared with slower‐growing grasses with less roots, regardless of fertilization treatment. Total N in clippings was highest in inland saltgrass and lower in buffalograss and bermudagrass, indicating that N was limiting for faster‐growing grasses. More research is needed to determine optimal N rates for establishing grasses that both optimize growth and minimize nitrate leaching. Core Ideas: Faster‐growing grasses had less nitrate leaching during establishment than slower ones. Irrigation treatments did not differ in root development. N content was lowest in clippings of faster‐growing grasses.